Prevention of postoperative recurrence of Crohn's disease - Van Loo, E; Dijkstra, G; Ploeg, R; Nieuwenhuijs, V (2012)
Background: Up to 75% of patients with Crohn's disease (CD) will have intestinal resection during their life. Most patients will, however, develop postoperative recurrence (endoscopic, clinical or surgical). Several medical and surgical strategies have been attempted to prevent postoperative recurrence. This review evaluates the efficacy of different drug regimens and surgical techniques in the prevention of clinical, endoscopic and surgical postoperative recurrence of CD. Methods: A literature search for randomized controlled trials on medical or surgical interventions was performed. The endpoints for efficacy were clinical, endoscopic and surgical recurrence. Meta-analyses were performed in case two or more RCTs evaluated the same drug or surgical technique. Results: Mesalamine is more effective in preventing clinical recurrence than placebo (P. =. 0,012), as well as nitroimidazolic antibiotics at one year follow-up (P. <. 0.001) and thiopurines (P. =. 0.018). Nitroimidazolic antibiotics are also more effective than placebo in preventing endoscopic recurrence (P. =. 0.037), as well as thiopurines (P. =. 0.015) and infliximab (P. =. 0.006). Budenoside, probiotics, Interleukin-10 nor any of the different surgical procedures showed any significant difference compared to placebo in postoperative recurrence rates of CD. Conclusion: Among the different drug regimens and surgical techniques, only thiopurines and nitroimidazolic antibiotics are able to reduce postoperative clinical as well as endoscopic recurrence of CD. Mesalamine and infliximab also seem to be superior to placebo in preventing clinical recurrence and endoscopic recurrence, respectively. There is a paucity of trials evaluating long-term follow-up and prevention of surgical recurrence of CD. © 2011 .